The language of newspapers - Conboy, Martin (Continuum, 2010)
Acknowledgements; Introduction: The social nature of newspaper language; 1. Society writes back; 2. Putting on a style: The contours of a public sphere; 3. Radical rhetoric: Challenging patterns of control; 4. Shaping the social market; 5. A message from America: A commercial vernacular; 6. Tabloid talk: Twentieth-century template; 7. Technology and newspaper language: The reshaping of public communication; Bibliography; Index.; This book charts the connections between the language of journalism in England and its social impact on audiences and social and political debates from the first emergence of periodical publications in the seventeeth century to the present day.ssIt extends work done on the language of the media to include an historical perspective, adding to wider contemporary debates about the social impact of the media.ss. It draws upon the field of historical pragmatics, while retaining a concentration on the development of a particular form of media language, the newspaper, and its role in refracti.; Includes bibliographical references and index